No Viral No Justice: A Criminological Review of Social Media-Based Law Enforcement from the Perspective of Progressive Law - Runturambi, Arthur Josias Simon; Aswindo, Munarni; Meiyani, Eliza (Jurnal IUS Kajian Hukum dan Keadilan, 2024)
The phenomenon of "no viral, no justice" emerges due to public distrust of the justice system, prompting people to "play judge" themselves on social media in the name of substantive justice, despite the risks of defamation and violations of the legal process. The purpose of this research is to analyze the “no viral, no justice” phenomenon arising from social media-based law enforcement and evaluate its harmony with the principles of progressive law. This normative legal research uses a conceptual approach, applying primary and secondary legal materials, a literature study for data collection techniques, and content analysis to describe the application of progressive legal concepts in social media-based law enforcement. Qualitative data analysis is carried out systematically to draw conclusions in accordance with the research problem formulation. The results show that the "no viral, no justice" phenomenon arises because law enforcement is influenced by public pressure due to viral cases on social media to be addressed immediately, thus creating the perception that non-viral cases mean no justice. This contradicts the principles of progressive law, which promotes the protection of human rights, substantive justice, and rejects discrimination. Law enforcement is also still not considered harmonious with progressive law because viral cases on social media are prioritized without considering justice holistically, while the principles of equality before the law and the presumption of innocence should still be upheld before public pressure comes into play.